Phenology of tree species in the Atlantic Rain Forest from Poço das Antas Biological Reserve, Rio de Janeiro, Brazil. - Pereira, Tânia Sampaio (2008)
Phenological studies are an important tool for the management of indigenous plant species, as they can support seed collection and seedlings production programs. This study aims to give information on features of the life cycle of some of the most important plant species participating in the forest succession in the Poço das Antas Biological Reserve, Rio de Janeiro, Brazil. Fifty-eight tree species with ecological and economical importance, as well as potentiality to recover degraded areas, were selected. Monthly records of phenological data were taken from April 1994 to March 1996, in order to associate climate records to changes in leafing, flowering and fruiting patterns. In order to support an Ecological Restoration Program, a calendar was set up for seed collection in the area. Most of the species showed an annual pattern for flowering and fruiting. Flowering was positively associated to high rainfall and temperature. Fruiting prevailed in periods before the rain season, while fruit resources were seen during the entire year.